Влияние русского языка на белорусские говоры (на примере полевых исследований в Мядельском pайоне Минской oбласти) - Żebrowska, Anna (Studia Rossica Posnaniensia, 2020)
The aim of this article is to describe the role of the Russian language in a multilingual environment, which is the Belarusian-Polish-Lithuanian borderland. The study pays particular attention to the influence of the Russian language on contemporary Belarusian dialects, in particular on the Central Belarusian dialect. Part of the Central Belarusian dialect is the dialect of Kamarova (Myadzel district, Minsk region), where I have conducted field research since 2010. The article provides an analysis of selected fragments from the interviews with local residents, indicating a significant impact of the Russian language (primarily at the lexical level) on the speech of the residents of Kamarova, regardless of their age, education, status, position, etc. Moreover, the long and continuing influence of the Russian language on Belarusian dialects, its strong position in Belarus and its high prestige suggest a change in the dialect of Kamarova, in which lexical elements of the Polish/ Lithuanian language are gradually being replaced by their Russian equivalents.